Testing Antioxidant And Antibacterial Activity Of Andaliman Fruit (Zanthoxylum Acanthopodium Dc.) Ethanol Extract With Abts Method (2,2'-Azino-Bis(3-Ethylbenz-Thiazoline-6-Sulfonic Acid) And Minimum Resistant Concentration - Agung Adha Witasa Dewana; Tan Suyono; Linda Chiuman; Sahna Ferdinand Ginting (CV. Inara, 2022)
Antioxidants are chemical compounds that can donate one or more electrons to free radicals, so that these free radicals can be quenched. There are two sources of antioxidants, namely natural and synthetic antioxidants. Andaliman (Zanthoxylum acanthopodium DC.) is one of the many spice plants found in Toba Samosir and North Tapanuli Regencies, North Sumatra. Andaliman plants grow at an altitude of 1,500 m above sea level. Apart from North Sumatra. This research using method experimental research when collecting and processing andaliman fruit, making simplicia, making ethanol extracts and examining antioxidant activity tests using the ABTS free radical scavenging method (2,2'-azino-bis(3-ethylbenz-thiazoline-6-sulfonic acid) and antibacterial activity. using the minimum inhibitory concentration method. Testing the antioxidant activity of the ethanol extract of andaliman fruit with the ABTS method using a UV-VIS spectrophotometer with a wavelength of 734 nm. the regression equation (y = 0.4619 + 20.226) obtained an IC50 value of 64.4598 mg/mL which can be classified as a strong antioxidant activity. The results of the antibacterial activity test of the ethanol extract of the andaliman fruit showed that the extract had antibacterial activity in the moderate category at a concentration of 300 mg/ml with an inhibition zone of 10.